Big Data and ICT Readiness Index for ASEAN Economic Community (Journal of Governance and Development (JGD), 2016)
ASEAN is undergoing a paradigm shift from Government-to-Government (G2G) to Community-to-Community (C2C) relationships with the emphasis on integration and collaboration. The relatively recent developments of Information and Communication Technology (ICT), especially Social Networks, Web 2.0, mobile technology, big data and its related technologies have become the main drivers of this paradigm shift. Big data optimizes capabilities process, high growth and diversified data that create value and knowledge for community within ASEAN in facing ASEAN Economic Community. This study assesses the ICT readiness of each of the ASEAN members to take advantage of the ICT development to build C2C integration and collaboration in facing big data era. The study reveals the score value of each country member to portray ICT readiness for the components of infrastructure development, human capital, people empowerment, innovation, and economic transformation. The paper shows the stages in ICT initiatives in the context of ASEAN and recommend ICT development for each country to eliminate the digital gap between members. It also proposes model of big data for ASEAN member country in supporting economic transformation.